IMPLEMENTASI PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA DALAM MERANCANG BASIS DATA - Didih Aditiyawarman (Jurnal Informatika, 2016)
AbstractDatabase design is one step in making data processing applications both desktop and web-based applications. There are several techniques that can be used to design a database, one of them with Entity Relationship Diagram techniques. It’s one of the techniques taught in the course of Database Design. In fact, many students who have difficulty in designing a database with this technique. The use of appropriate learning techniques to optimize learning of database actively, attractive and effective is needed. The method used in the learning process is problem-based learning methode. So, the authors conducted a study to examine how the use of Problem Based Learning as an effective method of learning the technique of designing a database with Entity Relationship Diagram. It’s descriptive research, and used the Pre-experimental design with one group pretest-posttest design. This study used a class as an experimental class. This research method describes the influence of problem-based learning model in the ability to design database with Entity Relationship Diagram in Information Management students at AMIK BSI Karawang. The research sample is taken from class 12.2D.15 and 20 students were taken as sample for testing and research. The hypothesis with ’t’ test showed that designing a database with Entity Relationship Diagram technique using problem based learning show better results than without using it. This shows that the implentation of problem-based learning in learning database design with Entity Relationship Diagram technique has a significant effect on the ability of students in designing database.  Keywords: Problem Based Learning, database, Entity Relationship Diagram